Performance and age of the fastest female and male 100-km ultramarathoners worldwide from 1960 to 2012 - Cejka, N.; Knechtle, B.; Rüst, C. A.; Rosemann, T.; Lepers, R. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this cross-sectional study was to investigate the change in 100-km running performance and in the age of peak performance for 100-km ultramarathoners. Age and running speed of the annual fastest women and men in all 100-km ultramarathons held worldwide between 1960 and 2012 were analyzed in 148,017 finishes with 18,998 women and 129,019 men using single, multivariate, and nonlinear regressions. Running speed of the annual fastest men increased from 8.67 to 15.65 km/h and from 8.06 to 13.22 km/h for the annual fastest women. For the annual 10 fastest men, running speed increased from 10.23 ± 1.22 to 15.05 ± 0.29 km/h (p < 0.0001) and for the annual 10 fastest women from 7.18 ± 1.54 to 13.03 ± 0.18 km/h (p < 0.0001). The sex difference decreased from 56.1 to 16.3% for the annual fastest finishers (p < 0.0001) and from 46.7 ± 8.7% to 14.0 ± 1.2% for the annual 10 fastest finishers (p < 0.0001). The age of the annual fastest men increased from 29 to 40 years (p = 0.025). For the annual fastest women, the age remained unchanged at 35.0 ± 9.7 years (p = 0.469). For the annual 10 fastest women and men, the age remained unchanged at 34.9 ± 3.2 (p = 0.902) and 34.5 ± 2.5 years (p = 0.064), respectively. To summarize, 100-km ultramarathoners became faster, the sex difference in performance decreased but the age of the fastest finishers remained unchanged at ~35 years. For athletes and coaches to plan a career as 100-km ultramarathoner, the age of the fastest female and male 100-km ultramarathoners remained unchanged at ~35 years between 1960 and 2012 although the runners improved their performance over time.